Adsorption of peroxidase from Raphanus sativus L onto alginate-guar gum matrix: Kinetic, equilibrium and thermodynamic analysis - Leite da Silva, Ana C. Santos Leite (2016)
This work explores the kinetics, equilibrium and thermodynamics of peroxidase adsorption onto spherical guar gum-alginate matrices. The effect of contact time, solution pH, initial protein concentration and temperature was studied in batch experiments. The results show that peroxidase adsorption increased with rising contact time and initial enzyme concentration, and was higher at pH 4.0. The kinetic processes can be predicted by both the pseudo-first-order rate kinetics and the pseudo-second-order rate kinetics. Equilibrium adsorption data were analyzed with different isotherm models. The experimental data fitted to the Freundlich model in agreement with the low energy activation, demonstrating the presence of a high physical and unspecific interaction between the enzyme and the matrix.